Fungsi Manajemen dalam Pengelolaan Pembelajaran Kurikulum Merdeka Belajar di Sekolah Umum - Anuli, Yahya Yunus; Damopolii, Mujahid (Jurnal Ilmiah AL-Jauhari: Jurnal Studi Islam dan Interdisipliner, 2023)
The curriculum as an educational programme (ideal curriculum) emphasises the operational learning process and becomes an important component in the national education system which is interrelated in an integrated manner to achieve national education goals. The purpose of this article is to analyse the management function in the management of independent learning curriculum learning in public schools. The approach used in this research is a qualitative approach. The results show that management functions can be distilled into three main functions, namely planning, implementation, and supervision. The stages of curriculum implementation: (1) Programme development, including annual, semester or quarterly, monthly, weekly, and daily programs. In addition, there is also a guidance and counseling program or remedial program; (2) Implementation of learning. That is the process of interaction between learners and their environment so that there is a change in behavior for the better; (3) Evaluation, a process carried out throughout the process of implementing the curriculum quarterly or semester as well as formative or summative final assessment includes an overall assessment as a whole for the purposes of evaluating curriculum implementation.